2013
DOI: 10.1007/s11934-013-0348-3
|View full text |Cite
|
Sign up to set email alerts
|

Urethral Lift for Benign Prostatic Hyperplasia: A Comprehensive Review of the Literature

Abstract: Current treatments for benign prostatic hyperplasia (BPH) include watchful waiting, medical therapy, and interventional procedures. The post-surgical complication profile and the early discontinuation of medical therapy are significant drawbacks of the established approach and stimulate the search for less-invasive approaches. Our aim is to provide a comprehensive review all available literature on prostatic urethral lift (PUL), presenting an overview of safety, indications, surgical technique and results of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
4
0
4
Order By: Relevance
“…22 The Urolift ® system emerges as a new therapeutic alternative that acts mechanically separating the prostatic lobes, thus avoiding the risks associated with surgery. 22 The Urolift ® system emerges as a new therapeutic alternative that acts mechanically separating the prostatic lobes, thus avoiding the risks associated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…22 The Urolift ® system emerges as a new therapeutic alternative that acts mechanically separating the prostatic lobes, thus avoiding the risks associated with surgery. 22 The Urolift ® system emerges as a new therapeutic alternative that acts mechanically separating the prostatic lobes, thus avoiding the risks associated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Böylece lateral loblar prostatın kapsülüne doğru çekilir (Şekil 2). Fibromusküler prostat kapsülü periüretral dokuya kıyasla gerilmeye dayanıklıyken periüretral doku daha esnek olabildiğinden implantın yerleştirilmesinden sonra tıkanıklığa neden olan prostat lobları laterale doğru yer değiştirerek prostatik üretranın açılması sağlanır (5).…”
Section: Uygulama Yöntemiunclassified
“…Eşlik eden üriner enfeksiyonu olan hastalarda da yabancı cisim kolonizasyon riski nedeniyle uygulanmamalıdır. Alfa redüktaz inhibitörlerinin 6 ay önce ve alfa blokerlerin en az bir hafta önce kesilerek olası devam eden etkilerinin yapılan işlemin sonucuna etkisi önlenmiş olmalıdır (5). PUA yöntemi literatürde 149 cm 3 hacminde prostata bile uygulanmasına rağmen, özellikle yöntemi öğrenme aşamasında 50 cm 3 'den büyük prostatlara önerilmemektedir (8).…”
Section: Endikasyonlarunclassified
See 1 more Smart Citation
“…The first, randomized controlled blinded trial demonstrated a reduction in American Urological Association Symptom Index from baseline by 4 points at 2 weeks, 11 points by 3 months, and this reduction remained stable to 1 year. A comprehensive literature review found that although PUL seems to offer a better IPSS improvement when compared to medical therapy, the result is inferior when compared with surgical therapy [17]. The reported advantages of PUL include a low complication profile, preservation of ejaculatory and erectile function, and minimal to no catheter requirement [14,15].…”
Section: Prostatic Urethral Lift (Urolift)mentioning
confidence: 99%